Bile duct structure: A sign of things to come? (2005)
Objective: The aim of the report is to highlight this difficult to-treat condition hitherto uncommon in our environment and warn of the likelihood of more to come with the rising incidence of gallstone in our sub region. Patient and Method: A case report of an 18-year-old male undergraduate patient. Result: A successful management with clinical, biochemical and radiological evidence (OTC and tubograms) despite inadequate investigative tool. Principal Conclusion: With the rising incidence of gall stones in our environment, it is imperative that the Trainee Surgeon must be schooled in common biliary surgery and help prevent this dreaded complication (bile duct stricture) and other sequelae of gall bladder surgery. A plea is also made for the provision of essential investigative tool to facilitate management of such cases in recognised centers.